Химическое изучение Artemisia tournefortiana Rchb. - Родичев, М.А. (Изд-во КарГУ, 2010)
Қазақстан флорасындағы Artemisia tournefortiana Rchb. өcімдігі жер беті бөлігінің химиялық компоненттері сипатталды. Осы өсімдіктен алғаш рет эфир майының негізгі компоненттері, жаңа сесквитерпенді лактоны турнефорин, сондай-ақ 6-деметокси-4'-O-метилкапилларизин флавоноиды бөлініп алынды. Some chemical components of the aerial part of plant of Kazakhstan population of Artemisia tournefortiana Rchb. were characterized. New sesquiterpene γ-lactone tourneforin from this species was isolated and the structure of their molecule was determined. The known flavonoid 6-demetoxy-4'-Omethylcapillarizine was identified, which isolated first time from this species and the main components of essential oil were determined.
Keywords: полынь; турнефоровская полынь; Artemisia tournefortiana Rchb.; эфирное масло; хромато-масс-спектрометрия